Listeria monocytogenes 10403S Alternative Sigma-54 Factor σL Has a Negative Role on Survival Ability Under Bile Exposure - Boonmee, Atsadang; Oliver, Haley F.; Chaturongakul, Soraya (Frontiers in Microbiology, 2021)
Listeria monocytogenes is a Gram-positive bacterium causing listeriosis in animals and humans. To initiate a foodborne infection, L. monocytogenes has to pass through the host gastrointestinal tract (GIT). In this study, we evaluated survival abilities of L. monocytogenes 10403S wild type (WT) and its isogenic mutants in alternative sigma () factor genes (i.e., sigB, sigC, sigH, and sigL) under simulated gastric, duodenal, and bile fluids. Within 10 min of exposures, only bile fluid was able to significantly reduce survival ability of L. monocytogenes WT by 2 logs CFU/ml. Loss of sigL (ΔL) showed the greatest bile resistance among 16 strains tested (i.e., WT, four single alternative  factor mutants, six double mutants, four triple mutants, and one quadruple mutant). To further investigate the role of L in bile response, RNA-seq was conducted to compare the transcriptional profiles among L. monocytogenes 10403S ΔBCH triple mutant (lacking sigB, sigC, and sigH genes; expressing housekeeping A and L) and ΔBCHL quadruple mutant (lacking all alternative sigma factor genes; expressing only A) strains under BHI and 1% bile conditions. A total of 216 and 176 differentially expressed genes (DEGs) were identified in BHI and bile, respectively. We confirmed that mpt operon is strongly σL-dependent. Interestingly, more than 80% of DEGs were found to be negatively regulated in the presence of σL. This result suggests the negative regulation by σL is important for bile survival and the roles of σL and σB might be in a seesaw model prior to host cell invasion.